Pengaruh Akuntabilitas, Kompetensi dan Independensi Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik di Surabaya - Aziz, Asmaul (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
This study aims to determine the influence of accountability, competence, and independence to quality audit of KAP in Surabaya. This research was comparative causal research. The population of this study is 77 auditors who work in 9 Public Accounting Firm in Surabaya. The sample of this study was 44 samples and used convenience sampling method as the data collecting procedure. The instrument that used was questionnaire method. Data analysis that used to test the hypothesis is multiple linear regression analysis, coefficient of determination, t test, F test and dominant test. The result of the research showed that there are positive and significant influence of Auditor Accountability to Audit Quality with determination coefficient equal to 0,138 and tcount 3,809 > ttabel 1,684, There is a positive and significant influence of Auditor Competence on Audit Quality with determination coefficient of 0,179 and tcount5,835> ttable 1.684 . There is a positive and significant influence of Auditor Independence on Audit Quality with determination coefficient of 0.710 and tcount 16.891 > ttable 1.684. There is positive and significant influence of Auditor Accountability, Competence and Independence of Auditor collectively to Quality Audit with coefficient of determination equal to 0,934 and price Fcount 203.690> Ftabel 2.84.